Divergent annulation of spiro[indoline-pyran] and fused (Epoxyetheno)indeno-furan from 1,2-diketone and 1-cyanoketone - Yadav, Maruti B.; Vagh, Sandip S.; Jeong, Yeon Tae (European Journal of Organic Chemistry, 2022)
A simple and efficient method for the construction of spiro[indoline-pyran] and fused (epoxyetheno)indeno[1,2-b]furan compounds from 1-cyanoketones and 1,2-diketone has been developed. The synthesis proceeded via the Knoevenagel and Michael adduct through intramolecular/Paal-Knorr cyclization under similar reaction condition. The less commonly used 1-cyanoketones and active carbonyl compounds served as the indole containing pyran and bicyclic furan source for the preparation of a new series of heterocyclic compounds. This heterocyclic structure allows one and more than one tetra-substituted carbon center and sequential hexa- and penta-cyclic core under very mild conditions and shows excellent chemo and regioselectivity. In addition, the synthesis of spiro[indoline-pyran] and (epoxyetheno)indeno[1,2-b]furan was demonstrated in a gram scale.
Keywords: Diverse synthesis; Intramolecular; Knoevenagel and Michael adduct; molecular diversity; Oxygen heterocycles; Paal-Knorr cyclization